Neurosociology: intrerdisciplinary field of science - Leposavić, Ivana; Veljković, Jasna (Sociološki pregled, 2023)
Neurosociology is a relatively new interdisciplinary field of science. It is a discipline that lies on the borders between sociology, social psychology, biology and neurosciences. This scientific field offers an opportunity for better understanding interactions between brain and interpersonal functioning by analyzing the influence of social factors on creating brain organization and its functions.
Keywords: neurosociology; social cognition; theory of mind